Empowering Coastal Communities: Training on Making Floating Nets - Mahmud Mustain; Wahyudi Wahyudi; Haryo Dwi Armono; Muhammad Zikro; Yeyes Mulyadi (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
Based on the results of the study program conducted by the Kangean Island Coastal Community with the theme: "Maritime Management Towards a Prosperous Fisherman Community" on Saturday, February 6, 2021, real follow-up is needed. Of the many problems that emerged from the study, the problem raised in this service was the lack of empowerment of coastal communities, resulting in a lot of neglected/neglected marine potential. Such as the potential of sea grapes, seaweed, crab cultivation, grouper, and others. The solution to this problem that will be given is to carry out training to coastal communities to improve the quality of Human Resources (HR) in terms of optimizing the potential that is still neglected. The training packages that have been delivered are; Making Floating Cages for Fish Cultivation in the Sea (Crab, Grouper, Tuna, etc.). The target that has been achieved is the courage of the training participants to carry out a realization trial in order to implement the results of the training. One training package, God willing, has been given in the form of a face-to-face online and conference where participants are gathered in one room. This is because there is still the shackles of the Covid-19 Pandemic. The training syllabus includes; Material Preparation, Set-up, and Measurement, Construction of the Main Structure, Installation of the Upper Frame Structure on the Floater/Floater, Road Installation on the Upper Frame Structure, Launching of the Floating Net Cage (KJA) to the Sea, Anchoring, Installation of Nets, and Finishing to be ready for seed anchorage. The implementation of the training has been during the working day. The training was also followed online throughout the East Java region. The practice of making charts or prototypes for marine fish farming and charts for floating cages for Crab and Grouper cultivation have been made by a group of fishermen in Bangkalan Regency.